Religiusitas, Koping Religius, dan Kesejahteraan Subjektif - Utami, Muhana Sofiati (Jurnal Psikologi, 2012)
The purpose of this research was to study the variables of religiosity, positive religious coping and negative religious coping as predictors of student’s subjective well-being. The subjects of this research were 166 college students. Their subjective well-being was measured by using the SWB-SLS Scale (Positive Affect, Negative Affect and Life Satisfaction at Campus) and the SWB-PLS (Positive Affect, Negative Affect and Personal Life Satisfaction). Religiosity Scale and Religious Coping Scale were used respectively to measure the religiosity and the positive and negative religious coping. Based on the parametric-statistic analysis with Pearson’s product-moment correlation indicated that there is a positive relationship between positive religious coping and student’s subjective well-being and a negative relationship between negative religious coping and student’s subjective well-being. However, it was not found that religiosity has relationship with student’s subjective well-being. Based on the multiple regression analysis, this research showed that the three variables can simultaneously become the predictors of student’s subjective well-being. The effective contribution of positive and negative religious coping is more significant than that of religiosity to student’s subjective well-being. Keywords: religiosity, positive religious coping, negative religious coping, subjective well being